The Animal Curator. Duchamp’s Inframince and Animality - Doove, Edith (Scenari, 2021)
Looking at seemingly curatorial activities by the bower bird is the starting point for this paper to explore the notion of the “animal curator”. Where Wolfe’s introduction to Serres’ The Parasite (2007) was earlier used to stress the necessity of “becoming minor” or “animal” in a curatorial context (Doove, 2017), this paper will further unpack this connection through a reading of Wolfe’s and Derrida’s observations on the posthuman and animal in the anthology Zoontologies (2003) in combination with Haraway’s Staying with the Trouble (2016) and Burrows’ and O’Sullivan’s Fictioning (2019). Finally, Duchamp’s concept of the inframince in connection with its interest for minor differences and potentialities is proposed as an operational tool as part of making the posthuman a possible solution to the impasse observed in this field. The inframince thus opens up an unexpected connection between Duchamp and animality.